2017
DOI: 10.1063/1.4974945
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between laser-induced damage densities of fused silica and average incubation fluences at 1064 nm in the nanosecond regime

Abstract: Correlation between laser-induced damage densities of fused silica and average incubation fluences at 1064 nm in the nanosecond regime The chronology of the physical processes involved in the nanosecond laser damage of fused silica is investigated at 1064 nm. From experiments realized with multiple longitudinal mode pulses, the correspondence between ring pattern damage morphology and the corresponding intensity profile allows the distinction of two damage phases: an incubation phase followed by a damage expan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Compared to the single longitudinal mode (SLM) pulses, the MLM laser pulses with temporal instabilities raise many issues about LID. In reported work, it exhibits strong differences of damage density [15,16] and morphology [17] at exit surface of silica between SLM and MLM regimes. The LID by MLM pulses at 1ω exhibits a clear systematic ring pattern due to the formation of an ionization front in surrounding air, which is not seen in SLM cases [17][18][19].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Compared to the single longitudinal mode (SLM) pulses, the MLM laser pulses with temporal instabilities raise many issues about LID. In reported work, it exhibits strong differences of damage density [15,16] and morphology [17] at exit surface of silica between SLM and MLM regimes. The LID by MLM pulses at 1ω exhibits a clear systematic ring pattern due to the formation of an ionization front in surrounding air, which is not seen in SLM cases [17][18][19].…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, in MLM regime, damage sites initiated at 3ω do not reveal such rings [20]. In terms of damage densities, at a given fluence of 1ω laser pulse, they are lower when produced with SLM pulses than those produced by MLM pulses [15]. However, an opposite behavior is observed at 3ω [16].…”
Section: Introductionmentioning
confidence: 91%
“…These negative results lead us to add a third optimization in the temporal domain. In the nanosecond regime, several studies have shown that the temporal pulse shape strongly influences the initiation [45][46][47][48][49] and the morphology [50,51] of laser-produced modifications in fused silica. Recent results showed that the temporal pulse shape is also a key parameter in femtosecond-laser-silicon interaction as perfect Gaussian temporal profile is not suitable for breakdown initiation inside silicon [26].…”
Section: B Nonlinear Propagation Simulationsmentioning
confidence: 99%
“…30 Silica is used in optical elements because of its antireection properties in high-power laser systems, which can improve the LIDT of the optical components. 31,32 Studies have mostly been conned to the laser parameters, including the pulse duration, 33 laser uence, 34 and wavelength, 35 as well as to the lm processing parameters including the thickness and organic groups 36 that affect the growth of the silica thin lm, such as its morphology and growth rate. However, studies have not modeled the relation between electromagnetic radiation and heat in the silicon dioxide thin lms.…”
Section: Introductionmentioning
confidence: 99%